Fuel Subsidy Reform in Malaysia: An Assessment on the Direct Welfare Impact on Consumers. (Global Business Management Review (GBMR), 2022)
This paper investigates the issue of fuel subsidy reform in Malaysia by analysing the direct welfare impact resulting from fuel subsidy removal. Using the Household Expenditure Survey 2004/2005 with a sample of 4227 households, the analysis is carried out by segregating households into 3 different income groups and the welfare impact due to subsidy cut is measured. The results show that the reduction in welfare due to higher price is larger for the middle 40% compared to the top and the bottom 40%. This is due to the fact that the middle 40% has a larger budget share on fuel. Fuel subsidies are found to be costly in protecting poor households due to substantial leakage of benefits to higher income group but the welfare loss for the lower income group due to subsidy cut is somewhat higher in relative term due to the smaller size of their income. Thus, while subsidy reform is undeniably necessary, our findings suggest that it must be carried out cautiously. Our study suggests that the reform must be accompanied with strategies and programs to mitigate the welfare loss, not only for the lower income but also the middle income group as well.